Localized surface plasmon resonance refractometer based on no-core fiber - Wang, Yan Ru (2019)
A novel optical fiber refractometer based on localized surface plasmon resonance (LSPR) is presented. The sensor was prepared by splicing a short segment of no-core fiber (NCF) between two multimode fibers. A gold nanoparticles (AuNPs) film was self- assembled on the sidewall of the NCF. When LSPR peak wavelength is used to investigate the refractive index (RI), sensitivity of 121.88 nm/RIU (R2 = 0.9107), 523.14 nm/RIU (R2 = 0.983) with limit of detection 1.64× 10-3 RIU, 3.82× 10−4 RIU over the RI range of 1.33-1.37 and 1.37-1.42, respectively. When normalized transmittance is used to investigate the performance of the sensor, sensitivity of -279 %/RIU (R2 = 0.9922) with limit of detection 4.61 × 10-5 RIU over the RI range of 1.33 -1.42.